2020
DOI: 10.1111/jgs.16727
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of Statins in Veterans Admitted to Nursing Homes near the End of Life

Abstract: BACKGROUND/OBJECTIVES: Geriatric guidelines recommend against statin use in older adults with limited life expectancy (LLE) or advanced dementia (AD). This study examined resident and facility factors predicting statin discontinuation after nursing home (NH) admission in veterans with LLE/AD taking statins for secondary prevention. DESIGN: Retrospective cohort study of Veterans Affairs (VA) bar code medication administration records, Minimum Data Set (MDS) assessments, and utilization records linked to Medicar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
0
20
0
1
Order By: Relevance
“…The main indication for the use of statins is the prevention of cardiovascular events, and usually, the need for statins is assessed individually depending on the patient’s risk profile [ 39 ]. In cancer patients with a limited life-expectancy, medications such as statins are usually discontinued when the benefit of drug use is assessed to be lower than its potential harms, and hence criteria for initiating statins differ compared to patients without cancer [ 40 ]. To manage the bias caused by the tendency to discontinue statins in late-stage terminal cancer, we ignored the discontinuation of statin use during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The main indication for the use of statins is the prevention of cardiovascular events, and usually, the need for statins is assessed individually depending on the patient’s risk profile [ 39 ]. In cancer patients with a limited life-expectancy, medications such as statins are usually discontinued when the benefit of drug use is assessed to be lower than its potential harms, and hence criteria for initiating statins differ compared to patients without cancer [ 40 ]. To manage the bias caused by the tendency to discontinue statins in late-stage terminal cancer, we ignored the discontinuation of statin use during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…One general approach frequently used to define discontinuation relies on identifying gap periods in medication use. Gap periods have included 7 days [ 16 ], 14 days [ 17 ], and 30 days [ 18 ] between drug fills in published end-of-life studies based on pharmacy dispensing and claims. Non-end-of-life studies have also used 60 days [ 19 ] or 90 days [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to small numbers, we excluded women ( n = 22 excluded). Finally, we excluded residents who received hospice care at or before the start of follow-up ( n = 301 excluded), based on the admission treating specialty or a treatment indicator from the MDS ( 3 , 4 ). We excluded hospice residents due to the high overall mortality rate, proximal inevitability of death, and small sample size, which reduced our ability to conduct stratified analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Potential overuse of medications ( 1 ) is well-documented among older nursing home (NH) residents with limited life expectancy (LLE) and those with dementia, with as many as 50% being exposed to at least one medication with uncertain benefit near end of life ( 2 ). Specifically, investigators of recent observational studies have identified a high prevalence of possible overuse of aspirin ( 3 ), statins ( 4 ), antihypertensives ( 5 ), and diabetes medications ( 6 ) in NH residents with advanced dementia (AD) or LLE. Efforts are needed to reduce the risk for adverse effects through deprescribing and deintensifying medications (i.e., reducing the dose or number of drugs).…”
Section: Introductionmentioning
confidence: 99%